Dietary zinc intake and mortality in patients with intestinal-type gastric cancer: A prospective cohort study in Korea - Kwak, Jung Hyun; Park, Chan Hyuk; Eun, Chang Soo; Han, Dong Soo; Kim, Yong Sung; Song, Kyu Sang; Choi, Bo Youl; Kim, Hyun Ja (Frontiers in Oncology, 2022)
Purpose: Current evidence regarding the association between zinc intake and gastric cancer (GC)-specific survival in patients with intestinal-type GC is lacking. Therefore, this cohort study investigated the association between zinc intake and GC mortality through follow-up on GC death among patients with intestinal-type GC and whether these effects differ according to the source of zinc intake. Methods: A total of 185 patients with intestinal-type GC were enrolled from two hospitals between 2002 and 2006. Their survival or death was prospectively followed up until December 31, 2016, through a review of medical records and telephone surveys. Results: A total of 178 patients were included and analyzed. The median follow-up period was 7.3 years. In the fully adjusted models, the highest tertile of total zinc intake showed a significantly lower GC mortality than the lowest tertile (hazard ratio, 0.26; 95% confidence interval: 0.10–0.70). In addition, the tertile of total zinc intake showed a dose-response association with GC mortality (p=0.015). Analysis of the source of zinc intake revealed that when zinc intake from staples (rice and noodles), animal, and plant food sources were combined, the results were similar to those of total zinc intake and GC mortality. Conclusion: Zinc intake through various foods may be effective in reducing GC mortality by achieving balance with other nutrients. Our results suggest that zinc improves the survival of patients with intestinal-type GC in Korea.